Satresnarkoba Efforts Through Guidance and Counseling to Prevent Drug Abuse in the Jurisdiction of Salatiga Police - Paramitha Aulia Putri Nandira (Advances in Police Science Research Journal, 2022)
This research is motivated by the increasing trend of drug abuse in the Salatiga Police jurisdiction due to the Covid-19 pandemic that hit Indonesia. The existence of a government policy to limit community activities outdoors makes the Salatiga Police Drug Research Unit unable to carry out guidance and counseling activities optimally. This study aims to analyze the implementation of guidance and counseling carried out by the Salatiga Police Narcotics Unit and the efforts that can be made through guidance and counseling to prevent drug abuse. This study uses a qualitative approach and field research methods. This study uses primary and secondary data sources, and is located in Salatiga City. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. Data collection techniques used interview, observation, and document studies. The concept used is the concept of Guidance and Counseling, Drug Abuse, and Narcotics Satres, while the theory used is the theory of Management and SWOT Analysis. The results showed that 1) The implementation of guidance and counseling carried out by the Salatiga Police Narcotics Unit had differences between before and during the pandemic so that it could not be carried out optimally; 2) The efforts made by the Narcotics Unit of the Salatiga Police are to carry out guidance and counseling activities by means of face-to-face in a limited manner, and to use communication media as an alternative to implementing activities without face-to-face meetings. The results of this study are expected to be useful for the Narcotics Satres of the Salatiga Police in particular and the community in general to reduce the number of drug abuse in the jurisdiction of the Salatiga Police. The findings are expected to be used as a constructive evaluation for the Polri institution.